Pengaruh Skeptisisme Profesional, Independensi dan Pengalaman pada Kinerja Auditor dengan Reward Sebagai Variabel Pemoderasi - Mia Prabawati, Ni Made; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi, 2018)
The purpose of this study is to determine the effect of professional skepticism, independence and experience on the performance of auditors with rewards as pememerasi variables. This research takes place at Public Accounting Firm in Bali Province. The number of samples in this study are 71 auditors and determined by nonprobability sampling method that is purposive sampling. Data collection method used in this research is questionnaire. Data analysis used MRA.  The results of this study indicate that professional skepticism, independence and experience positively affect the auditor's performance. The results of this study also show that rewards strengthen the relationship of professional skepticism, independence, and experience on auditor performance. To improve the performance of auditors and provide performance that is more qualified, it requires professional skepticism and high independence and experience in every auditor who works in Public Accounting Firm Bali, as well as the rewards provided also need attention. Keywords: auditor performance, professional skepticism, independence, experience and reward.